Cueing the youth athlete during strength and conditioning: a review and practical application - Barillas, S. R.; Oliver, J. L.; Lloyd, R. S.; Pedley, J. S. (Strength and Conditioning Journal, 2021)
Verbal cues are tools used by practitioners in developing a youth athlete's motor skill abilities. External cues may optimize athletic performance and movement competencies in adults with trends for youth athletic populations following suit. However, maturation, training age, and cognitive age may interact with the efficacy of cues used. To better assist practitioners working with youth, this article reviews current empirical evidence on how youth populations respond or may respond to cues and offers practical applications.